Dynamics of Urbanization in the City of Rabat-Morocco, Which Sustainable Transition? - Elhamdouni Soraya; Idrissi Youssef; Cherkaoui Essediya; Nounah Abderrahman; Khamar Mohamed (Civil and Environmental Engineering)
In a world where many new concepts and phenomenon have emerged, cities are the first territorial entities to be concerned and impacted by changes in their various spatial, social, economic, political, urban planning and environmental components. In this article, we focus on the urban evolution of Rabat, a city with historical, political, social, economic and environmental issues at stake.